PERANCANGAN SISTEM MONITORING DAN KONTROL KUALITAS AIR SERTA PEMBERIAN PAKAN OTOMATIS PADA BUDIDAYA LELE BIOFLOK BERBASIS INTERNET OF THINGS - Gde Dendy Denhero; I Putu Elba Duta Nugraha; Lie Jasa (Program Studi Teknik Elektro UNUD, 2021)
Cultivation with a biofloc system has several advantages and disadvantages. Biofloccatfish cultivation technology is a technique to balance carbon and nitrogen levels in water toimprove pond water quality. However, cultivators must make observations in the cultivationpond water more often and carefully in order to prevent the increase in nitrogen levels. So,referring to this, a monitoring and control system for water quality and automatic feeding onbiofloc catfish cultivation was designed. The research was conducted by applying theexperimental method, in which the system is divided into three subsystems, namely waterquality monitoring, automatic water replacement, and automatic feeding. The results obtainedfrom conducting this research are in the form of tool trial data which will then be compared withdata from the program that has been made, as well as performance data from the automaticwater replacement subsystem and automatic feeding subsystem which were carried out for 5consecutive days. The conclusion of this research is that the design of a water qualitymonitoring and control system and automatic feeding on biofloc catfish cultivation based on theInternet of Things has been successfully made. In the automatic water replacement subsystem,the average relative error is 2.75%. In the automatic feeding subsystem, the average differencein feeding time is 14.5 seconds and the average relative error is 3.3%.